2012
DOI: 10.1371/journal.pone.0047797
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Roles of Cytokinins and Cytokinin Signaling in Response to Potassium Deficiency in Arabidopsis

Abstract: Potassium (K) is an important plant macronutrient that has various functions throughout the whole plant over its entire life span. Cytokinins (CKs) are known to regulate macronutrient homeostasis by controlling the expression of nitrate, phosphate and sulfate transporters. Although several studies have described how CKs signal deficiencies for some macronutrients, the roles of CKs in K signaling are poorly understood. CK content has been shown to decrease under K-starved conditions. Specifically, a CK-deficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(68 citation statements)
references
References 39 publications
2
63
0
3
Order By: Relevance
“…[25][26][27] Exogenous application of cytokinins has been reported to increase the stress-tolerance capacity of plants indicating a beneficial effect of CKs in the regulation of plants adaptation to environmental stresses. Thus several studies with abiotic stresses like heavy metals, drought, salt and high temperature have reported that CKs could be involved in regulating antioxidant defence, while information on regulation of antioxidant metabolism under UV-B stress by CKs is lacking.…”
Section: -24mentioning
confidence: 99%
“…[25][26][27] Exogenous application of cytokinins has been reported to increase the stress-tolerance capacity of plants indicating a beneficial effect of CKs in the regulation of plants adaptation to environmental stresses. Thus several studies with abiotic stresses like heavy metals, drought, salt and high temperature have reported that CKs could be involved in regulating antioxidant defence, while information on regulation of antioxidant metabolism under UV-B stress by CKs is lacking.…”
Section: -24mentioning
confidence: 99%
“…15 The K C nutritional status is linked to the ethylene, cytokinin, jasmonic acid and auxin signaling pathways, thus leading to developmental and physiological alterations. [16][17][18] Moreover, it presumably influences plant disease resistance. 19 When grown under limiting K C supply, total root size was reduced in 26 investigated natural Arabidopsis accessions, but the degree of reduction and the root architectural response to K C limitation strongly differed between accessions.…”
Section: Introductionmentioning
confidence: 99%
“…Phytohormones needed for the plant growth and development and also play an important role in nutrient response . In response to nutrient stress, different phytohormones involve in nutrient homeostasis, e.g., auxin, cytokinin (CK) (N, P, K, and S stress), abscisic acid (ABA), gibberellic acid (GA) (P stress) (MaruyamaNakashita et al 2004;Franco-Zorrilla et al 2005;Rubio et al 2009;Ruffel et al 2011;Nam et al 2012;Rigas et al 2013;Shen et al 2013). Auxin, CK, and ABA intimately linked with N signaling and involved in regulating N acquisition, RSA modification in response to N stress (Kiba et al 2011).…”
Section: Introductionmentioning
confidence: 99%